Method of message authentication code formation based on permutations - Фауре, Эмиль Витальевич; Швыдкий, Валерий Васильевич; Щерба, Валентина Александровна (Ukrainian Information Security Research Journal, 2015)
The task of controlling the integrity of transmitted messageswhich is provided by the use of message authenticationis relevant for constructing of protected telecommunicationssystems. Given the growth of computing meansproductivity, and improving the methods of hacking ofinformation protection systems including protectionagainst false data imposing requirements for messageauthentication methods and means increase. In this paperthe structural diagram of device of random permutationssequence formation is developed and shown. On thebasis of this device construction principles the methodand device of message authentication code formation isproposed. The essence of the method lies in the fact thatas a message authentication code is used a part of large dimension permutation symbols in some chosen order.This permutation is formed from the sequence of charactersof the message converted into a sequence of related numbers in factorial number system. To hide the law offormation of message authentication code a replaceabletransformation key is used. The resistance of permutationand message authentication code generated from it whentrying to break a key by "brute force" is determined.